THE EXTENT TO WHICH THE COMPREHENSIVE CONCEPT OF FINANCIAL CONTROL IS APPLIED TO PUBLIC FUNDS IN IRAQ (IRAQI A STUDY IN LEGISLATION) - Aizdihar Jasim Muhamad; Mithal Kreem Kadhim AL- Zubady; Ahmed Hassan Ali AL –Mamoori (Scholar Express Journals, 2023)
The purpose of this study is to answer many questions, the first of which is what is the comprehensive concept of public money control? Is it applied in Iraq? The second question, what are the reasons for the failure of the system of control over public funds in Iraq to achieve its objectives? We have addressed two requirements, the first is the theoretical framework for defining the concept of comprehensiveness of financial control, and the second is the reasons why financial control does not achieve its objectives. Therefore, the descriptive analytical approach was followed for the data obtained from constitutional articles, laws and websites to verify the hypothesis that the comprehensive concept of control over public funds needs to be defined. It is clear in order to achieve the objectives of control in accordance with the sustainable development approach. The importance of this research comes from the importance of money and its role in achieving the well-being of society. The scientific importance of the research lies in providing the library with one of the scientific sources that clarify the meaning of the comprehensive concept of financial control. The most important findings of the research lie in the reasons Which hindered the agency from carrying out its basic function, including reasons related to the lack of a comprehensive concept of oversight, others related to the formulation of laws regulating the oversight of public funds, and others related to the work systems of the oversight bodies and the prevailing work environment in Iraq
Keywords: comprehensive concept of oversight; financial control law; public money; corruption